The General Theory of Second Best - Lipsey, R. G.; Lancaster, Kelvin (Review of Economic Studies, 1956)
Journal Article The General Theory of Second Best Get access R. G. Lipsey, R. G. Lipsey London Search for other works by this author on: Oxford Academic Google Scholar Kelvin Lancaster Kelvin Lancaster London Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 24, Issue 1, 1956, Pages 11–32, https://doi.org/10.2307/2296233 Published: 01 July 1956